Synthesis and Characterization of Ferric Silicate Composite using Precipitation Method - Fatayoga; Taufik Rahmandika Adi Sutrisno; Ketut Sumada; Srie Muljani; Suprihatin (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
This research examines the synthesis of ferric silicate composite using precipitation method. This research aims to synthesise and characterise the composite by examining the influence of initial silica concentration and precipitation pH. For the preparation of the composite, precursors such as ferric chloride (FeCl3) and sodium silicate (Na2SiO3) were used as iron and silica sources, respectively. Dissolved ferric chloride solution added dropwise into sodium silicate solution to bring the precipitation pH to a desired value. Then, the precipitate was filtered, washed, and calcined. Synthesized composites were analyzed using X-ray fluorescence (XRF) and surface area analysis (SAA) through Brunauer-Emmett-Teller (BET) method. The result shows that the highest characterisation is found for different sample parameters. Highest silica content up to 53.70%, surface area up to 116.3180 m²/gr, highest pore diameter up to 70.8653 nm, and highest pore volume up to 0.3993 cm³/gr. The correlation between initial silica concentration and precipitation pH and the textural properties of the composite was observed as increasing initial silica concentration, which affected the composite characteristics, including increasing final silica content, larger surface area, pore diameter, and pore volume. Meanwhile, increasing precipitation pH leads to increasing final silica content, smaller surface area and larger pore diameter. Synthesized ferric silicate composite shows that this material has porous characteristics that can be applied as catalysts, filters, membranes, ion exchangers, and adsorbents. Contribution to Sustainable Development Goals (SDGs):SDG 9: Industry, Innovation and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 13: Climate Action